Broken markets : a user's guide to the post-finance economy - Mellyn, Kevin (Apress : Distributed by Springer-Verlag, 2012)
"I would sleep better if I knew that Bernanke, Geithner, Bachus, Sen. Tim Johnson, Obama and Romney all kept dog-eared copies of Kevin Mellyn's Broken Markets on their nightstands. ... Mellyn's work is a fascinating, important, and eminently good read and should inform the debate on overhauling the U.S. and global financial regulatory systems and sustainable macro fiscal and monetary policy."--Eric Grover, in his review of Broken Markets in The American Banker Broken Markets allows the intelligent non-specialist to understand and navigate the ongoing worldwide aftermath of the 2008 financial market meltdown. The key theme of the book is how the leading financial institutions and the political leadership of the U.S. and European Union have failed us and set the stage for continued market turmoil. It explainswhat this means for investors, borrowers, society in general, and the financial-services industry. Former banker Kevin Mellyn focuses on providing readers with clear and simple explanations of the forces at work and the potential consequences for their future prosperity. As this book makes clear, what's coming is a world in which high structural unemployment and flat or declining real income is likely-not to mention a diminished retirement financial safety net. The book therefore provides actionable information for protecting wealth and making prudent investment decisions in an economy that is nothing like the one that has sustained us for decades. As a forward-looking narrative about rapidly changing events and volatile markets and politics, Broken Marketswill provide no single prediction about the future but rather describe alternative scenarios and provide the reader with signposts to watch out for in deciding which reality is actually unfolding. Unlike most books written by journalists on global finance, the scenarios and signposts described will be largely based on the lessons of financial and political history rather than breaking news. This book: Tells you in plain language how today's financial system threatens your livelihood and wealth Tells you why and how governments worldwide, with some notable exceptions, are taking actions likely to make things worse instead of better Explains how the leading financial institutions lost their way during the bubble years and how they can find the path back to prosperity and value to society Tells you what life will be like in a 'post-finance' economy and how you can protect your wealth